Ecomorphology and resource use by dominant species of tropical estuarine juvenile fishes - Pessanha,André Luiz Machado (2015)
Eleven ecomorphological attributes and diet of seventeen juvenile fish species were examined to test the hypothesis that morphological patterns determine resource uses in estuarine habitats. Species were separated according to the apparatus to food capture and habitat use (benthic or pelagic) in three different groups: (1) a group with depressed fish body, strong caudal peduncle and enlarged pectoral fins; (2) a second group laterally flattened with a wide protruding mouth, and (3) a third group strongly flattened with small pectorals fins. The following six trophic groups were organized based on prey categories: Zooplanktivores, Benthivores, Omnivores, Detritivores, Macrocarnivores and Insectivores. Significant results (PERMANOVA) between ecomorphological indices and habitat and between ecomorphological indices and trophic groups were found. These data indicate that similarity of ecomorphological forms, which minimize the influence of environment and partitioning of food, would help facilitate the co-existence of these fish when they are abundant in this tropical estuary.